2017
DOI: 10.5505/tjtes.2017.63668
|View full text |Cite
|
Sign up to set email alerts
|

Bridge treatment for early cholecystectomy in geriatric patients with acute cholecystitis; percutaneous cholecystostomy

Abstract: BACKGROUND:The main cause of acute cholecystitis (AC) is gallstones, and the incidence of gallstones in elderly patients is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Of these, 22 studies reported on outcomes following early interval LC 7,[15][16][17][18][19][20][21][22][23][24][25]36,[43][44][45]47,[49][50][51][52][53] , and 22 studies following late interval LC 3,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]45,46,48 . Three studies reported and compared outcomes in both groups 25,36,45 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of these, 22 studies reported on outcomes following early interval LC 7,[15][16][17][18][19][20][21][22][23][24][25]36,[43][44][45]47,[49][50][51][52][53] , and 22 studies following late interval LC 3,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]45,46,48 . Three studies reported and compared outcomes in both groups 25,36,45 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Bazı çalışmalar yüksek riskli hastalarda akut kolesistit için perkütan safra kesesi drenajının kolesistektomi olmadan tek başına tedavi olarak kabul edilebileceğini öne sürmektedir [12][13]. Ancak genel kabul edilen tedavi tekrarlayan kolesistitleri önlemek için PSD ile hastalığın akut döneminden kurtulduktan sonra daha güvenli olan elektif kolesistektomiyi yapmaktır [14,15]. Literatürde hastaların% 43 ile 94'nün PSD'den sonra kolesistektomiye gittiği bildirilmiştir [5].…”
Section: Köprüleme Tedavisi Ve Işlem Zamanıunclassified
“…The use of PCT as a bridge to future CCY has shown mixed results in single center studies, partly due to the heterogeneity in study populations and small sample size [ [6] , [7] , [8] ]. The 2018 Tokyo Guidelines for the treatment of gallbladder and biliary pathology classifies cholecystitis into grade I-III, with grade III defined as acute pathology with additional organ dysfunction.…”
Section: Introductionmentioning
confidence: 99%